The Role of Artificial Intelligence in Hindering the Implementation of International Humanitarian Law - Al-Saigh, Mohammed; عبد القادر, بيناك (Journal of Legal Sciences, 2026)
The international system is undergoing a profound structural transformation driven by the rapid advancement of artificial intelligence technologies, particularly when integrated into military contexts and the management of armed conflicts. Autonomous weapons systems, algorithms capable of making lethal decisions, and systems that assist in intelligence gathering and analysis have become part of the reality of modern warfare. This transformation raises critical questions about the extent to which international humanitarian law, in its current form, is capable of regulating the conduct of belligerent parties and ensuring compliance with the fundamental principles established to protect civilians and reduce human suffering.This research examines the impact of artificial intelligence in hindering the implementation of international humanitarian law by analyzing a set of key manifestations, most notably: the increased complexity of the principle of distinction and the difficulty of applying proportionality during attacks, the absence of effective human oversight, algorithmic opacity, and the fragmentation of legal responsibility chains. The study also addresses the structural gaps within the framework of international humanitarian law in relation to rapid technological development, in addition to challenges related to accountability, transparency, bias, and the lack of interpretability. The research concludes with the necessity of reassessing the international legal framework and developing new approaches that align with the nature of smart weapons and autonomous systems, to ensure that artificial intelligence does not become a tool that amplifies violations rather than a means of ensuring compliance with the law.